Colonial dynamics limit climate adaptation in Oceania: Perspectives from the Marshall Islands. (March 2020) - Bordner, Autumn S.; Ferguson, Caroline E.; Ortolano, Leonard
Highlights: The Marshall Islands is existentially threatened by climate change. Colonial conduct–including past forced migrations–has increased Marshallese vulnerability to climate change. Marshallese leaders wish to adapt in place to protect sovereignty and identity. Persistent colonial dynamics work to divest Marshallese of sovereignty over adaptation. Sovereignty over adaptation decision-making should be returned to Marshallese in order to prevent catastrophic loss. Abstract: In the island states of Oceania, colonial power dynamics profoundly shape climate vulnerability and response. Largely as a result of their colonial history, island nations are dependent on outside funders to adapt to climate change, reproducing colonial subordination by depriving island states of sovereignty over their adaptation strategies. We empirically demonstrate the sovereignty-depriving effects of the current adaptation process through a case study from the Republic of the Marshall Islands (RMI). Recent scholarship suggests that, without swift and large-scale adaptation, RMI will be uninhabitable by mid-century, threatening a population-scale forced migration. Our research indicates that Marshallese leaders are committed to adapting in place in order to preserve national identity and sovereignty, but they view reliance on external funding as a major barrier to implementing the measures that could enable RMI to survive in the face of climate change. Marshallese decision-makers in this study perceive that aid institutions discount the existential implications of failing to pursue aggressive adaptation, assuming instead that migration is inevitable, economically rational, and even desirable. Such a proposal is particularly painful given the history of forced migration in RMI caused by U.S. nuclear weapons testing there. These neocolonial dynamics not only deprive island states of sovereignty over their adaptation strategies but also threaten permanent abrogation of national sovereignty and selfdetermination through loss of a habitable territory. To uphold global commitments to decolonization and human rights, our research indicates the need to return sovereignty over climate adaptation decision-making to affected states.